Machine diagnosis of chronic obstructive pulmonary disease using a novel fast-response capnometer - Talker, L; Neville, D; Wiffen, L; Selim, AB; Haines, M; Carter, JC; Broomfield, H; Lim, RH; Lambert, G; Weiss, ST; Hayward, G; Brown, T; et al. (BioMed Central, 2023)
Background Although currently most widely used in mechanical ventilation and cardiopulmonary resuscitation, features of the carbon dioxide (CO2) waveform produced through capnometry have been shown to correlate with V/Q mismatch, dead space volume, type of breathing pattern, and small airway obstruction. This study applied feature engineering and machine learning techniques to capnography data collected by the N-Tidal™ device across four clinical studies to build a classifier that could distinguish CO2 recordings (capnograms) of patients with COPD from those without COPD.